1988
DOI: 10.1159/000242825
|View full text |Cite
|
Sign up to set email alerts
|

Respiratory Failure Caused by Intratracheal Saline: Additive Effect of Xanthine Oxidase

Abstract: Administration of physiological saline or drugs together with saline into the airways is becoming common clinical practice. However, there are few studies on possible side effects. We have studied the effects of saline, saline plus xanthine oxidase, and saline plus xanthine oxidase plus superoxidase dismutase on lung-thorax compliance and on arterial blood gases in anesthetized, paralyzed guinea pigs, ventilated for 2.5 h. Saline bolus (2–3 ml isotonic saline/kg body weight) into the airways reduced the compli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
1

Year Published

1989
1989
2009
2009

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 11 publications
0
6
0
1
Order By: Relevance
“…Subscores for atelectasis were significantly lower in SOD-pretreated animals than in non-SOD-treated animals, but there were no differences between treatment groups: 3 (2-4) in group I, 2 (1-3) in group II, and 4 (3)(4)(5) in controls. Also, subscores for edema were significantly lower in SOD-pretreated animals than in non-SODtreated animals: 2 (2-4) in group I, 2 (1-2) in group II, and 4 (2-4) in controls.…”
Section: Histopathologic Findings Of Lung Sectionsmentioning
confidence: 80%
See 1 more Smart Citation
“…Subscores for atelectasis were significantly lower in SOD-pretreated animals than in non-SOD-treated animals, but there were no differences between treatment groups: 3 (2-4) in group I, 2 (1-3) in group II, and 4 (3)(4)(5) in controls. Also, subscores for edema were significantly lower in SOD-pretreated animals than in non-SODtreated animals: 2 (2-4) in group I, 2 (1-2) in group II, and 4 (2-4) in controls.…”
Section: Histopathologic Findings Of Lung Sectionsmentioning
confidence: 80%
“…Using neonatal piglets which closely resemble newborn human infants with regard to anatomic and physiologic aspects of the lungs, we recently established an animal model of acute lung injury similar to ARDS [3]. Previous studies, also including our study, showed the prophylactic effects of superoxide dismutase (SOD) pretreatment in alleviating acute lung injury caused by endotoxin in rats [4][5][6][7]. In the present study, we assessed the efficacy of endotracheal SOD administration for acute lung injury induced experimentally in neonatal piglets.…”
Section: Introductionmentioning
confidence: 99%
“…A series of experimental studies have shown that the free radical-generating system, hypoxanthine-xanthine oxidase, can damage the lung [7,[21][22][23]. These experimental data are supported by the results of Russell and Cooke [24] showing that premature infants who subsequently developed CLD had higher plasma hypoxanthine levels at birth than those who did not develop CLD.…”
Section: Effect Of Increased Oxidative Load On the Lungmentioning
confidence: 85%
“…Normally, such fea tures should not be present 4 days after birth, while regenerative alveolar epithelium should be present, at least focaily. Similarly, in cases Biol Neonate 1996;70: [21][22][23][24][25][26][27][28]who survived 10, 12, and 13 days, epithelial necrosis and hyaline membrane formation were extensive, along with focal regenerative type II hyperplasia and mild septal fibrosis. In the case who survived 22 days, irregular atel ectasis and persistent alveolar cell necrosis were present; the latter should not be present after 15 days.…”
Section: Discussionmentioning
confidence: 99%
“…Many factors may be involved in the po tential mechanisms responsible for the in creased incidence of alveolar haemorrhage in surfactant-treated infants, including baro trauma, circulatory overload, capillary fragili ty, and free oxygen radical damage [20][21][22][23][24][25]. Free oxygen radicals play a key role in the pathogenesis of neonatal lung lesions.…”
Section: Discussionmentioning
confidence: 99%